PELATIHAN PEMBUATAN E-MODUL BERBASIS FLIPBOOK TERINTEGRASI DENGAN MODEL RME UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA DI MTSN 1 BUKITTINGGI - Handican, Rhomiy; Sari, Nola; Khaidir, Chritina; Aryasandy, Nensy (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2023)
Improving the quality of mathematics learning at the madrasah level requires contextual and interactive media innovations. This community service activity aims to enhance teachers’ competence in developing flipbook-based e-modules integrated with the Realistic Mathematics Education (RME) approach to improve students’ conceptual understanding. The training was conducted at MTsN 1 Bukittinggi through a three-day participatory workshop method involving 12 mathematics teachers. Evaluation results indicated a significant improvement in participants’ understanding of RME and their technical skills in creating flipbook e-modules. Moreover, the resulting e-modules met high-quality standards in terms of content, interactivity, and integration of realistic contexts. This activity demonstrates that the combination of flipbook and RME can effectively support a more meaningful and contextual transformation of mathematics learning